Evaluation of a Native Preparation of HCV Core Protein (2-122) For Potential Applications in Immunization, Diagnosis and Mab Production - MR Aghasadeghi; SM Sadat; A Budkowska; AR Khabiri; S Amini; G Bahramali; SR Naddaf; F Roohvand (Tehran University of Medical Sciences, 2006)
Infection with hepatitis C virus (HCV) is a worldwide problem. Among HCV proteins, core antigen (Ag), besides its importance for diagnostic application is a prime candidate for component of a vaccine. Herein, we report results of studies on production of the hydrophilic domain of core Ag (2-122) in native conformation by an arabinose induction system in E.coli and the primary characterization of this recombinant protein for applications in diagnosis, immunization and mAb production. Recombinant core (r-Core) was able to detect anti-core antibodies in HCV positive serum samples in a dilution rate of 1/3200. It was also capable to elicit a potent anti-HCV humoral immune response in BALB/c mice. Finally, we established two stable clones of hybridoma which shown to produce specific and sensitive mAbs against the core protein. HCV core was able to elicit a broad range of antibody specificities depending on the immunogen conformation. Therefore, it may be possible to get new mAbs with higher affinities towards native conformation of core Ag.